2023
DOI: 10.1177/17579139231180751
|View full text |Cite
|
Sign up to set email alerts
|

Economic recession, illicit drug use and the young population: a systematic literature review and meta-analysis

Abstract: Aims: Economic recessions impact on drug use through different channels, with potential conflicting outcomes. Previous studies have reached mixed outcomes, and a clear and comprehensive picture is difficult to depict. Methods: We use a systematic review of literature – conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines – and a hierarchical mixed-effects meta-analysis to provide a comprehensive quantitative assessment of the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Main five main transmission mechanisms can be identified (Casal et al, 2023). With the income effect mechanism, a reduction in disposable income means that fewer goods are purchased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main five main transmission mechanisms can be identified (Casal et al, 2023). With the income effect mechanism, a reduction in disposable income means that fewer goods are purchased.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed empirical analysis is therefore required by type of drug, specific social-subpopulations, and user characteristics (for instance, age) (Casal et al, 2023;Dom et al, 2016;De Goeij et al, 2015;Nagelhout et al, 2017). Casal et al (2023) systematically reviewed the scientific literature and ran a meta-analysis to assess the impact of economic recessions on the use of illicit drugs. They concluded that economic downturns have a larger impact on the people who use drugs more frequently, tending to increase its prevalence, especially among groups of high-risk users.…”
Section: Introductionmentioning
confidence: 99%